Protective effects of L-arginine against aluminium chloride-induced testicular damage in rats - Yildirim, Sena Ozcan; Colakoglu, Neriman; Kaya, Seyma Ozer (Wiley, 2022)
Aluminium (Al) is a toxic metal with frequent exposure because it is a common element in nature and is found in many products used in daily life. L-arginine is a semi-essential amino acid that is involved in many biochemical pathways in the body and has antioxidant effects. The current research evaluated the possible protective effects of L-arginine against aluminium chloride (AlCl3) induced testicular damage. In this animal-based experimental study, 28 male Wistar Albino rats were separated into four groups: control, Al (20 mg/kg/day Al), Al + L-arginine (20 mg/kg/day Al + 50 mg/kg/day L-arginine), and L-arginine (50 mg/kg/day L-arginine). All applications were carried out intraperitoneally (i.p.) for 4 weeks. The histopathological changes caused by exposure to Al in the testicular tissue and the protective effects of L-arginine were investigated by using biochemical, histochemical, immunohistochemical [4-hydroxynonenal (4-HNE) and 8-hydroxy-2 '-deoxyguanosine (8-OHdG)] and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay techniques. The testicles in the AlCl3 group showed increased 4-HNE, 8-OHdG expressions, apoptotic index, and abnormal sperm content, while serum testosterone levels, sperm motility, and sperm number were decreased (p < 0.05). Furthermore, histomorphometric examinations of testicular tissue indicated significant structural impairments such as vacuolization in the seminiferous tubule epithelium, edema, and vascular congestion in the interstitial area (p < 0.05). However, the structural alterations were largely ameliorated in the Al + L-arginine group (p < 0.05). Thus, L-arginine, which is an antioxidant, may protect against the harmful effects of Al and may help improve male fertility.
Keywords: 4-HNE; 8-OHdG; aluminium; L-arginine; testicular damage